The Reliability of Child-Friendly Race-Attitude Implicit Association Tests - Williams, Amanda; Steele, Jennifer R. (Frontiers in Psychology, 2016)
Implicit attitudes are evaluations that are made automatically, unconsciously, unintentionally, or without conscious and deliberative processing (Gawronski & DeHouwer, 2014; Nosek et al., 2007). For the last two decades implicit measures have been developed and used to assess people’s attitudes and social cognition, with the most widely used measure being the Implicit Association Test (IAT; Greenwald et al., 2003). This measure has been used extensively to assess racial biases and a number of studies have examined the reliability of the IAT when administered to adults (Bar-Anan & Nosek, 2014; Cunningham et al., 2001; Gawronski, 2002; Greenwald et al., 2003; Nosek et al., 2005; Nosek & Smyth, 2007). In recent years, the IAT has also been modified for use with children. Despite the potential of this measure to provide insight into the early emergence of implicit racial attitudes, little is known about the psychometric properties of these modified child-friendly IATs (Child-IATs). In the current research we examined the internal consistency of race-attitude Child-IATs when either reduced (Study 1) or traditional-length (Study 2) versions were administered to children (Studies 1 & 2) and adults (Study 2). We also examined the test-retest reliability of this measure with both child and adult participants (Study 2). We found that these measures demonstrate an internal consistency comparable to what has been seen in previous research with adults. In addition, the internal consistency of traditional-length Child-IATs completed in succession depended on the order in which they were completed; the first Child-IAT demonstrated higher internal consistency than the second for both children and adults (Study 2). Finally, we provide the first evidence that the test-retest reliability of the Child-IAT is comparable to what has been found previously with adults (Study 2). The implications of these findings for future research examining children’s implicit social cognition are discussed.